2018
DOI: 10.1186/s12879-018-3259-6
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of norovirus GII.P16-GII.2 strains in patients with acute gastroenteritis in Huzhou, China, 2016–2017

Abstract: BackgroundIn late 2016, an uncommon recombinant NoV genotype called GII.P16-GII.2 caused a sharp increase in outbreaks of acute gastroenteritis in different countries of Asia and Europe, including China. However, we did not observe a drastic increase in sporadic norovirus cases in the winter of 2016 in Huzhou. Therefore, we investigate the prevalence and genetic diversity of NoVs in the sporadic acute gastroenteritis (AGE) cases from January 2016 to December 2017 in Huzhou City, Zhejiang, China.MethodsFrom Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 33 publications
(43 reference statements)
6
19
0
Order By: Relevance
“…(Figure 5A,B). Particle integrity and carbohydrate binding profiles were screened for each of these mutants, and while the VLP were indistinguishable from the native GII.2 Chapel Hill strain via electron microscopy, all lost carbohydrate binding to both A and B saliva ( Figure 5C), supporting previous reports demonstrating that amino acids within the P2 domain are important for HBGA recognition [32,51]. To better understand residues on the GII.2 capsid that were important for mAb and HBGA recognition, a panel of 5 GII.2 Chapel Hill VLPs were designed with alanine mutations in regions where microvariation was observed between the prototypic 1976 and Chapel Hill GII.2 strains.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…(Figure 5A,B). Particle integrity and carbohydrate binding profiles were screened for each of these mutants, and while the VLP were indistinguishable from the native GII.2 Chapel Hill strain via electron microscopy, all lost carbohydrate binding to both A and B saliva ( Figure 5C), supporting previous reports demonstrating that amino acids within the P2 domain are important for HBGA recognition [32,51]. To better understand residues on the GII.2 capsid that were important for mAb and HBGA recognition, a panel of 5 GII.2 Chapel Hill VLPs were designed with alanine mutations in regions where microvariation was observed between the prototypic 1976 and Chapel Hill GII.2 strains.…”
Section: Resultssupporting
confidence: 81%
“…(Figure 5A,B). Particle integrity and carbohydrate binding profiles were screened for each of these mutants, and while the VLP were indistinguishable from the native GII.2 Chapel Hill strain via electron microscopy, all lost carbohydrate binding to both A and B saliva ( Figure 5C), supporting previous reports demonstrating that amino acids within the P2 domain are important for HBGA recognition [32,51].…”
Section: Resultssupporting
confidence: 81%
“…We found that GII.2[P16] viruses caused an increase in the number of norovirus outbreaks during winter 2016-17. The first GII.2[P16]positive sample was detected in August 2016 in Guangdong Province (36,37), and the number subsequently increased, with GII.2[P16] accounting for 70%-100% of norovirus outbreaks during winter 2016-17 in different provinces (38)(39)(40). Previous studies suggested that reemerging GII.2[P16] virus most likely evolved from strains emerging during 2012-2013 (41).…”
Section: Discussionmentioning
confidence: 99%
“…The peak in this study was in December, when Shenzhen began to turn cold, and March, when temperature began to turn warm, which is suspected that climate changes have an impact on NoV transmission. The NoV outbreak usually occurs in hospitals, nursing homes, schools, child care centers, hotels and other semi-enclosed places [34][35][36]. A study in United States reported 3,960 NoV outbreaks between 2009 and 2013 and found that long-term care homes were the most frequent sites of NoV outbreaks [37].…”
Section: Hbga-binding Pro Le Epitopes Predicted and Epitope A To E Smentioning
confidence: 99%